2004
DOI: 10.1021/jf0303621
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Scavenging Behavior of Antioxidant Compounds of Sesame (Sesamum indicum L.) in DPPH System

Abstract: The free radical scavenging capacity (RSC) of antioxidants from sesame cake extract was studied using the 2,2-diphenyl-1-picrylhydrazyl radical (DPPH(*)()) on a kinetic model. Pure lignans and lignan glycosides isolated from methanolic extract by preparative HPLC were used in the study. To understand the kinetic behavior better and to determine the RSC of sesame antioxidants, the second-order rate constant (k(2)) was calculated for the quenching reaction with [DPPH(*)] radical. The k(2) values of the sesame an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
141
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(150 citation statements)
references
References 21 publications
4
141
1
4
Order By: Relevance
“…Accumulating evidence suggests that the protective effects of SO against oxidative damage could be attributed to its antioxidative properties [9,11,24] . The antioxidant activity of SO could be attributed to its phenolic lignans-type compounds namely sesamol, sesamin and sesaminol [6] . These antioxidant compounds have been found to possess antioxidant effects against oxidative damage induced by cupper in vitro study [10] and endotoxin lipopolysaccharide [8,24] and ischemiareperfusion [12] in rats.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence suggests that the protective effects of SO against oxidative damage could be attributed to its antioxidative properties [9,11,24] . The antioxidant activity of SO could be attributed to its phenolic lignans-type compounds namely sesamol, sesamin and sesaminol [6] . These antioxidant compounds have been found to possess antioxidant effects against oxidative damage induced by cupper in vitro study [10] and endotoxin lipopolysaccharide [8,24] and ischemiareperfusion [12] in rats.…”
Section: Resultsmentioning
confidence: 99%
“…These include p-coumaric acid [4] , garlic acid [2] , erdosteine [5] and carvedilol [1] . Sesame Oil (SO) is extract from the plant Sesamum indicum (HS), family: Pedaliaceae [6] . SO offers protection over blood pressure, lipid profiles and lipid peroxidation in hypertensive patients [7] .…”
Section: Doxorubicinmentioning
confidence: 99%
“…Much research evidence suggests that the protective role of sesame oil against oxidative stress through its antioxidant mechanism (Kaur & Saini, 2000;Nakano et al, 2002;Hsu & Liu, 2004). It has been identified that presence of antioxidative principles like sesamin, sesamol and sesaminol might be a responsible components for its protective action (Suja et al, 2004). Therefore, the protection against myocardial IR injury in the treated rats is attributable to enhanced endogenous antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…Sesame is an important commodity supporting various industries and produce oil which is low in saturated fat (Suja, Jayalekshmy, & Arumughan, 2004). Sesame is normally self-pollinated species and a composite of various homozygous individuals in populations (Furat & Uzun, 2010).…”
Section: Introductionmentioning
confidence: 99%